Loxoscelism: Cutaneous and Hematologic Manifestations - Ngan Nguyen; Manjari Pandey (Advances in Hematology)
Background. Brown recluse spider (BRS) envenomation can lead to significant morbidity through severe local reaction and systemic illness including acute hemolytic anemia, rhabdomyolysis, disseminated intravascular coagulopathy (DIC), and even death. We aim to describe the clinical features and the roles of antibiotics and steroids in the treatment of loxoscelism. Methods. We retrospectively identified nine patients (pts) at our institution who were admitted with moderate to severe loxoscelism. A chart review was performed to highlight important clinical features and effect of interventions. Results. Nine pts (age 18 to 53) presented with fever (6), rash (9), pain/swelling (4), and jaundice (2). Of these, 6 pts had antecedent spider bites documented. Five pts were discharged from Emergency Room (ER) with oral antibiotics for “cellulitis” and were readmitted with severe systemic symptoms, with almost half (45%) of the pts being admitted to the intensive care unit. The most common admission diagnosis was sepsis secondary to cellulitis (6). Four pts developed worsening dermonecrosis, and 3 received prompt incision and drainage (I&D) with debridement. Hemolytic anemia developed around day 5 after spider bite (average); the lowest mean hemoglobin level was 5.8g/dL, with average drop of 3.1 g/dL. Direct antiglobulin test (DAT) (for both complement and surface immunoglobulin) was positive in 4 out of 9 patients. Four pts received glucocorticoid therapy for their hemolytic anemia. The use of steroid and intravenous immunoglobulin (IV Ig) did not seem to show a difference in the time of recovery although those who received steroids required less blood transfusion (2.1 units less). All pts had a complete recovery within two weeks. Conclusion. Treatment of systemic loxoscelism involves aggressive supportive care including appropriate wound management, blood transfusions, intravenous fluid replacement, and appropriate antibiotic coverage. It is unclear at this time if glucocorticoids or IVIg has any beneficial impact on the treatment of severe loxoscelism.